N-terminal fragments of titin in urine as a biomarker for eccentric exercise-induced muscle damage - Shota Yamaguchi; Katsuhiko Suzuki; Kazue Kanda; Junichi Okada (Japanese Society of Physical Fitness and Sports Medicine, 2020)
N-terminal fragments of titin in urine have been proposed as a noninvasive marker of muscle damage, but there are no data on its time course after 96 h. The aims of this study were to investigate the time course of urinary titin N-terminal fragment (UTF) following eccentric exercise and the subsequent correlations between UTF and other muscle damage indices. Seventeen healthy young men performed 30 maximal isokinetic eccentric exercises at the elbow flexors. Muscle soreness (SOR), range of motion (ROM), maximal voluntary isometric contraction (MVIC), creatine kinase (CK), and UTF were sampled before, immediately after, and 24-144 h after exercise. The changes and correlations were analyzed with one-way ANOVA and Spearman's rank correlation analysis. All the measured parameters showed significant differences from their pre-exercise values at 24 h or later after exercise (P < 0.05). UTF showed significant correlation with MVIC (r ≤ -0.485) at 24 h and later, with SOR (r ≥ 0.549) at 48 h and later, with ROM (r ≤ -0.485) at 48 h and later, and with CK (r ≥ 0.647) at all time points. UTF reached peak value at 96 h after the exercise and had not recovered completely at 144 h. Because UTF was highly correlated with the other muscle damage indices, especially CK, throughout the measurement period, it may be as useful an indicator of muscle damage as CK obtained from blood.